Kajian Produk Halal Farmasi Dalam Perspektif Islam Dan Kemuhammadiyaan - Sri Rahmawati; Oman Fathurohman sw (An-Najat, 2024)
The halal industry has now advanced and developed quite rapidly. In the beginning, the main focus was halal food, but has now expanded to other fields, such as medicines and medical devices. It is very important to maximize promising opportunities and potential. However, the increase in public interest in halal pharmaceutical products is not commensurate with the availability of halal pharmaceutical products in Indonesia. Therefore, not all generic medicines sold on the market freely have a halal logo or certification, so it is hoped that pharmaceutical products are products that have been labeled halal for consumers so that the products are standardized as halal and safe for use among the public. The aim of this research is to examine halal products from an Islamic and Muhammadiyah perspective. With an in-depth evaluation of these two perspectives, it will provide a comprehensive conception of the importance of halal pharmaceutical products with specific guidelines that can be adopted by various organizations to ensure that pharmaceutical products consumed by Muslims in accordance with sharia principles. This research uses qualitative methods with the type of library research related to the production of halal products as well as the perspective of halal products according to Islam and Muhammadiyah.